1996
DOI: 10.1002/(sici)1097-0126(199612)41:4<419::aid-pi631>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hard Segments of Polyurethane on Cell Growth

Abstract: Polyurethanes (PU) with suitable soft segments have been found to be good blood-compatible polymers and have attracted much attention recently. In this study, various molar amounts of 4,4'-methylene bisphenyl isocyanate reacted with poly(tetramethy1ene oxide) were synthesized to explore the optimal ratio of hard/soft segments for cell attachment and proliferation in in uitro systems. Differential scanning calorimetry and dynamic mechanical analysis were used to determine the physical properties, hydrogen bondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There are many factors that affect blood adhesion. The microphase separation resulting from the hydrophilic/hydrophobic nature of a material's surface is one factor determining its blood compatibility, but other basic surface propertiesincluding the surface roughness, free energy, electric charge, and polarization distribution -also can exert their effects [10,11,58].…”
Section: Relative Index Of Platelet Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many factors that affect blood adhesion. The microphase separation resulting from the hydrophilic/hydrophobic nature of a material's surface is one factor determining its blood compatibility, but other basic surface propertiesincluding the surface roughness, free energy, electric charge, and polarization distribution -also can exert their effects [10,11,58].…”
Section: Relative Index Of Platelet Adhesionmentioning
confidence: 99%
“…Polyurethanes are frequently used in artificial hearts, vascular prostheses, and many types of catheters in various clinical applications. Hydrophilic/ hydrophobic microdomain structures, such as those of polyurethane, generally display higher blood compatibility [10,11]. Grasel and Cooper reported that materials exhibiting a greater amount of phase separation had low platelet and fibrinogen deposition levels [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophilic/hydrophobic microdomain structures, such as those of polyurethane, generally display higher blood compatibility. 24,25 The growing commercial importance of polyurethane materials emphasizes the need for the study of polyurethane formation with respect to parameters such as chemical properties; micro-, macro-, and nanostructures; reagent concentrations; reaction media; and catalysts. Maji and Bhowmick reported micro-and nanostructured PUs based on various hyperbranched polymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…From the biomedical point of view, polyurethanes are frequently used in the biomedical and pharmaceutical fields, in drug delivery systems, artificial hearts, vascular prostheses, and various types of catheters in clinical applications. Hydrophilic/hydrophobic microdomain structures, such as those of polyurethane, generally display higher blood compatibility. , The growing commercial importance of polyurethane materials emphasizes the need for the study of polyurethane formation with respect to parameters such as chemical properties; micro-, macro-, and nanostructures; reagent concentrations; reaction media; and catalysts. Maji and Bhowmick reported micro- and nanostructured PUs based on various hyperbranched polymers. , Until now, there are only a few literature references on polyurethane acrylate. ,, …”
Section: Introductionmentioning
confidence: 99%